Performing rice farming rituals by Penampang Kadazan of East Malaysia: Between sacred ritual and secular performance - Hussin, H. (2008)
The rituals of rice farming amongst Penampang Kadazan essentially affirm the continuance of abundant harvest, family and household security over evil vibes and evil wind, and the permanency of residential guardian spirit, miontong. For a protracted balance of all the forces within miontong spatial domain, spiritual abodes contracted to the performance space are supplicated through the ritual cleansing and appeasement of musical instruments (drums and gongs) and performative aspect of female shamans, bobohizan and her entourage. These are the sacred rituals of monogit or cooling down of the heightened temperament, the emblem of Kadazan's people sacred and cultural identities. It has survived through extant practices by the Penampang Kadazan on the ground of sacredness and inviolability. However, performing sacredness becomes less efficacious when the emblems of this rice farming rituals become the signifiers of cultural performity in secular events, namely, Kaamatan, or Harvest Festival. This paper looks into performative dichotomies and contestations of Penampang Kadazan's perceptions of performing the sacred in secular spaces through the discourses of cultural anthropology, theater, and ethnography.